F (x) = 8 (x + 1) ^ 2- (3x + 3) ^ 2'nin standart formu nedir?

F (x) = 8 (x + 1) ^ 2- (3x + 3) ^ 2'nin standart formu nedir?
Anonim

Cevap:

#f (x) = - ^ x-2-2x 1 #

Açıklama:

Fonksiyonu standart formda yeniden yazmak için, parantezleri genişletin:

#f (x) = 8 (x + 1) ^ 2- (3 x + 3) ^ 2 #

#f (x) = 8 (X + 1) (x + 1) - (3 x + 3) (3 x + 3) #

#f (x) = 8 (x ^ 2 + 2x + 1) - (9 x ^ 2 + 18x + 9) #

#f (x) = 8x ^ 2 + 16x + 8-9x ^ 2-18x-9 #

#f (x) = 8x ^ 2-9x ^ 2 + 16x-18x + 8-9 #

#f (x) = - ^ x-2-2x 1 #